The mental health implications of street sex work: a literature review - Carey, Mekele (2009)
Background: Over decades, divergent discourses have debated the existence of prostitution. It remains the subject of conflicting theoretical and moral opinion. In the United Kingdom, the criminal justice system is the dominant figure involved in managing prostitution and their public ‘nuisance’. Street prostitutes have been at the forefront of those affected by this response. This punitive approach has lead to their health needs, and consequently their mental health needs, being somewhat overlooked. Aim: To explore the mental health needs of street prostitutes and assess whether factors associated with street prostitution expose those involved to psychiatric distress. Method: A literature review using Hek et al’s (2000) 7 stage framework for systematically searching and reviewing the literature. Results: Two primary associated factors were found to have both direct and indirect implications on the mental health of street prostitutes; these were ‘substance misuse’ and ‘trauma, violence and abuse’. These factors also indirectly perpetuated sexual health problems by increasing prostitute risk-taking behaviours. Conclusion: Factors associated with street sex work significantly increase the risk of street prostitute’s experiencing psychiatric distress. The current climate in which sex work exists does not cater for their needs. An appropriate service response is required to address their substantial and complex mental health needs.